MATHEMATICAL LITERACY THROUGH PROBLEM-BASED LEARNING: A SYSTEMATIC LITERATURE REVIEW OF INTERVENTION EFFECTIVENESS - Rahma Rahima DB; Ahmad Farham Majid; Nursalam Salam; Andi Dian Angriani (Universitas Muhammadiyah Lampung, 2025)
The Problem-Based Learning (PBL) model has been widely applied as an alternative in improving students' mathematical literacy, especially in the midst of low literacy achievement at various levels of education in Indonesia. Through a systematic review of 36 empirical articles published between 2016 and 2025, it was found that PBL consistently has a positive impact on reasoning skills, problem-solving, and the application of mathematical concepts in real-life contexts. The success of this approach is also influenced by various contextual factors, such as students' thinking styles, the role of teachers in facilitating learning, and the use of digital technology. The findings confirm that PBL is an effective learning strategy in building mathematical literacy, as well as making an important contribution for educators and policymakers in developing a more contextual, adaptive, and meaningful learning approach.